Direct “Cystoscopic” Approach for Arthroscopic Decompression of an Intraosseous Ganglion of the Lunate - Deepak N. Bhatia, M.S.(Orth), D.N.B.(Orth) (Arthroscopy Techniques, 2015)
Intraosseous ganglion cysts (IOGs) are uncommon lesions of the carpal bones and can present with persistent pain and stiffness of the wrist. Surgical decompression is recommended, and a variety of approaches to decompress symptomatic IOGs of the wrist have been described. We describe an arthroscopic approach that can be performed with only 2 portals and offers excellent access for visualization and instrumentation. The procedure involves creating a 3.2-mm tunnel into the lunate cyst; this is performed through the dorsal non-articular surface of the lunate, under direct vision, and the position is confirmed with fluoroscopy. A 2.4-mm arthroscope is passed through the drill hole, and a direct “cystoscopic” view of the IOG is obtained. Biopsy of the cyst contents is performed under direct vision, and small-joint shavers and burrs are used for effective debridement. Advantages of this technique are actual visualization of the pathology, complete intracystic debridement, and simultaneous treatment of any coexistent intra-articular pathology. In addition, the minimal 3.2-mm lunate tunnel access maintains the structural integrity of the lunate and reduces the need for additional bone graft supplementation.